In-depth analysis of eight susceptibility loci of primary angle closure glaucoma in Han Chinese. (January 2021) - Shi, Haihong; Chen, Yunxia; Lu, Hong; Zhu, Rongrong; Zhang, Junfang; He, Mengxuan; Guan, Huaijin
Abstract: Primary angle closure glaucoma (PACG) is a multifactorial disease with genetic predisposition. Primary angle closure (PAC) is the early stage of PACG and they share the same anatomical characteristics. We aimed to examine whether the PACG associated-genetic loci identified previously by genome-wide association study (GWAS) were also related to primary angle closure disease (PACD) in Han Chinese. This cross-sectional case-control study consisted of 232 PAC, 264 PACG and 306 controls. Eight single-nucleotide polymorphisms (SNPs) of PACG susceptibility loci within PLEKHA7, COL11A1, PCMTD1-ST18, EPDR1, CHAT, GLIS3, FERMT2, DPM2-FAM102A were genotyped using participants' blood samples. We excluded 3 SNPs for PAC analysis because the data has been reported using the same sample set. Anatomical parameters such as axial length (AL), anterior chamber depth (ACD) and lens thickness (LT) were included as phenotypes for the association analysis. Allelic and genotypic model tests were performed. Three among the eight SNPs were found to be significantly associated with PACG, e.g. PLEKHA7 rs11024102 in additive, dominant and recessive model; and both CHAT rs1258267 and DPM2-FAM102A rs3739821 in dominant model. CHAT rs1258267 showed marginal association with PAC in dominant model. Anatomical parameters were not found to link to the eight SNPs after Bonferroni multiple test correction. Our data suggest that PLEKHA7 and DPM2-FAM102A might exert effect in the late stage of the PACD, while CHAT may play a broad role in both early and late stages of the PACD. Highlights: PLEKHA7 and DPM2-FAM102A might exert effect in the late stage of the angle-closure disease. CHAT may play a broad role in both early and late stages of the PACD. ACD was the most important anatomic risk factor for PACG.